2020
DOI: 10.2176/nmc.oa.2019-0139
|View full text |Cite
|
Sign up to set email alerts
|

Operating Costs of Full-endoscopic Lumbar Spine Surgery in Japan

Abstract: For full-endoscopic lumbar discectomy, operating costs are also important because expensive equipment are necessary. We surveyed the operating costs of surgical equipment necessary for full-endoscopic surgery together with surgical procedure reimbursement fees. A total of 295 cases of full-endoscopic surgery via a transforaminal approach were retrospectively analyzed. We calculated the frequency of damage and the unit purchase price of devices such as endoscopes, and surgical instruments such as grasping force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Uniportal FESS was originally developed for the treatment of lumbar disc herniation and has recently been used for LSCS. 19 - 21 ) Technical refinements and the development of new instruments have expanded the scope of target diseases indicative for FESS. However, there are few studies on the use of uniportal FESS for the treatment of L5/S1 LFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniportal FESS was originally developed for the treatment of lumbar disc herniation and has recently been used for LSCS. 19 - 21 ) Technical refinements and the development of new instruments have expanded the scope of target diseases indicative for FESS. However, there are few studies on the use of uniportal FESS for the treatment of L5/S1 LFS.…”
Section: Discussionmentioning
confidence: 99%
“… 13 - 18 ) In contrast, uniportal full-endoscopic spine surgery (FESS) was originally developed for the treatment of lumbar disc herniation and has recently been used for spinal canal stenosis. 19 - 21 ) Full-endoscopic laminectomy via the translaminar approach (FEL-TLA) has been developed for the treatment of LFS. 22 , 23 ) In the present study, we retrospectively compared the operative outcomes of two operative procedures (ME-LIF and FEL-TLA) and clarified the advantages and disadvantages of these approaches.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, research has demonstrated that the costs of expendables alone make endoscopic discectomy financially unsustainable. 17 Aside from financial costs, there are also costs to both patients and surgeons during the learning curve. The learning curve for spinal endoscopy is substantial, considered steep for even experienced surgeons, ostensibly due to the lack of flexibility in instrumentation and 2-dimensional visualization.…”
Section: Nomentioning
confidence: 99%
“…Before a surgeon embarked a journey for fellowship in endoscopic spine surgery, he should check with the local vendors and community for availability of these specialized endoscopic equipment to make decision on where he should focus on training. As it is costly to set up the equipment required for endoscopy, sufficient volume of cases is needed to make a business case for funding when presenting to hospital management 39) . In microscopic tubular spine surgery, the retractor tube is fixed to the table after confirmation of position under fluoroscopic guidance.…”
Section: Endoscopic Drill and Energy Systemmentioning
confidence: 99%